DYNAMIC SIMULATION MODEL FOR SUSTAINABLE MUNICIPALITY DEVELOPMENT IN VIDZEME REGION, LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Authors in this research paper publish the results of system dynamic simulation modelling in the field of sustainable development planning, monitoring and evaluation for all 26 Latvia Vidzeme region municipalities. As the most notable research outcome, authors created original socio-technical system dynamic simulation model in STELLA modelling environment valid for sustainable development evaluation purposes. After successful verification and validation process of this model authors reached the significant results for improved methodology of dynamic systems evaluation process reliability of sustainable development in Vidzeme region municipalities. Methodology, proposed by authors roots into the quantitative statistical data analysis and system dynamic process simulation modelling.